2013
DOI: 10.1007/s00394-013-0618-3
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of conjugated linoleic acid isomers into porcine erythrocytes

Abstract: During supplementation with equivalent amounts of CLA isomers, their proportion in membranes of porcine erythrocytes increases with time, with higher proportion of c9, t11-CLA. CLA isomers probably differently incorporate into different cell membranes at different species which could explain its various biological functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The fact that the plasma FA profile is the first medium to mirror dietary changes, and that CE represents the greatest fraction of all lipids in plasma, explains why trans-10,cis-12 CLA could only be detected in this compartment. Studies in humans (Burdge et al, 2005) and porcine EM (Malovrh et al, 2014) showed preferential uptake of the cis-9,trans-11 CLA isomer when both cis-9,trans-11 and trans-10,cis-12 CLA were administered in the same doses. This may explain why we could not detect trans-10,cis-12 CLA in the EM of the investigated cows.…”
Section: Abmentioning
confidence: 98%
See 1 more Smart Citation
“…The fact that the plasma FA profile is the first medium to mirror dietary changes, and that CE represents the greatest fraction of all lipids in plasma, explains why trans-10,cis-12 CLA could only be detected in this compartment. Studies in humans (Burdge et al, 2005) and porcine EM (Malovrh et al, 2014) showed preferential uptake of the cis-9,trans-11 CLA isomer when both cis-9,trans-11 and trans-10,cis-12 CLA were administered in the same doses. This may explain why we could not detect trans-10,cis-12 CLA in the EM of the investigated cows.…”
Section: Abmentioning
confidence: 98%
“…In addition to PL in cell membranes, PL and CE in plasma are a large reservoir for EFA that supply organs and tissues and influence their functions. Incorporation of FA varies between distinct blood lipid pools, and follows fluctuationinduced changes from late pregnancy to early lactation (Christie, 1981;Malovrh et al, 2014). Essential fatty acids such as ALA and LA cannot be synthesized by mammals, including ruminants, and must be delivered by food (Palmquist, 2010).…”
Section: Introductionmentioning
confidence: 99%